Judaism, Christianity, and Islam: The problem of “Abrahamic religions” and the possibilities of comparison - Boyd, Samuel L. (Religion compass, 2019)
Judaism, Christianity, and Islam have long been known as “Abrahamic religions,” and the comparative study of these three religious traditions has occupied scholars focusing on a variety of time periods from antiquity to modernity. Recent research has begun to question, or at least to complicate, the label “Abrahamic religions,” opening up a host of new avenues of inquiry when examining the history and development of Judaism, Christianity, and Islam. In this article, I explore the relationship between popular and scholarly modes of understanding these religions. I examine the role of religious competition as a framework through which to research Judaism, Christianity, and Islam. I offer concluding thoughts regarding why this framework is beneficial not only to scholars of religion but also to lay readers for understanding why this field of comparative scholarship matters to them.